Intellectual Disability and Assistive Technology: Opening the GATE Wider - Boot, Fleur Heleen; Dinsmore, John; Khasnabis, Chapal; MacLachlan, Malcolm (Frontiers in Public Health, 2017)
The World Health Organisation has launched a program to promote Global Cooperation on Assistive Technology (GATE). The GATE program’s objective is to improve access to high quality, affordable assistive technology for people with varying disabilities, diseases and age related conditions. As a first step, GATE has developed the Assistive Products List, a list of priority assistive products based on addressing the greatest need at population level. A specific group of people who can benefit from user appropriate assistive technology are people with intellectual disabilities. However, the use of assistive products by people with intellectual disabilities is a neglected area of research and practice: and offers considerable opportunities for the advancement of population health and the realization of basic human rights. It is unknown how many people with intellectual disabilities globally have access to appropriate assistive products and which factors influence their access. We call for a much greater focus on people with intellectual disabilities within the GATE program and the challenges that are to be considered.